Dental fluorescence: Potential forensic use - Da Silva, Ricarda Duarte; da Silva, Marcos André Duarte; de Oliveira, Osmir Batista [UNESP]; Melo, Ana Cláudia Moreira; de Oliveira, Rogério Nogueira (Elsevier, 2013)
In cases of identification of bones, skeletal segments or isolated bones, searching for biotypologic diagnostic data to estimate an individual's age enables comparing these data with those of missing individuals. Enamel, dentin and pulp undergo remarkable changes during an individual's life. The enamel becomes more mineralized, smoother and thinner, and deteriorates because of physiological and pathological factors. Dental pulp decreases in volume due to the deposition of secondary dentin; thus, the dentin becomes thicker with time. In natural teeth, the fluorescence phenomenon occurs in dentin and enamel and changes in those tissues may alter the expression of the natural tooth color. The aim of this study was to assess the correlation between age and teeth fluorescence for individuals from different age groups. The sample consisted of 66 randomly selected Brazilians of both genders aged 7-63 years old. They were divided into 6 groups: Group 1 - aged 7-12 years, Group 2 - aged 13-20 years, Group 3 - aged 21-30 years, Group 4 - aged 31-40 years, Group 5 - aged 41-50 years and Group 6 - aged between 51 and 63 years. Upper right or left central incisors were used for the study. Restored and aesthetic rehabilitated teeth were excluded from the sample. The measurement of tooth fluorescence was carried out via computer analysis of digital images using the software ScanWhite DMC/Darwin Systems - Brazil. It was observed that dental fluorescence decreases when comparing the age groups 21-30, 31-40, 41-50 and 51-63 years. The results also showed that there is a statistically significant difference between the groups 41-50 years and 21-30 years (p=. 0.005) and also among the group 51-63 years and all other groups (p< 0.005). It can be concluded that dental fluorescence is correlated with age and has a similar and stable behavior from 7 to 20 years of age. It reaches its maximum expected value at the age of 26.5 years and thereafter decreases. © 2013 Elsevier B.V.
Keywords: Age estimation; Fluorescence; Forensic dentistry; Human identification; adolescent; adult; age; Brazilian; child; correlation analysis; dentistry; digital imaging; ethnic group; female; fluorescence analysis; forensic identification; human; image analysis; imaging software; incisor; male; normal human; priority journal; school child